2014
DOI: 10.1620/tjem.233.175
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Progression Is Associated with Accumulation of Th17 Lymphocytes in Tumor Tissues and Increased Serum Levels of Interleukin-6

Abstract: Colorectal cancer is a significant worldwide health problem, and an altered immunoresponse plays an important role in colorectal tumorigenesis and cancer progression. T helper 17 (Th17) lymphocytes (a subgroup of CD4 + T cells), together with the related cytokines, such as interleukin (IL)-6 and IL-17A, participate in cancer-related immunity. In this study, we measured the percentage of Th17 cells in peripheral blood mononuclear cells (PBMCs) and the levels of IL-17A and IL-6 in serum samples or tumor tissues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Serum levels of TNFa, IL1b, IL6, IL8, and IL17A are higher in patients with colorectal cancer compared with healthy controls (39,(68)(69)(70). IL6 is additionally associated with increased tumor size, tumor stage, metastases, and decreased survival (39).…”
Section: Inflammation and Vitamin D In Patients With Colorectal Cancermentioning
confidence: 99%
“…Serum levels of TNFa, IL1b, IL6, IL8, and IL17A are higher in patients with colorectal cancer compared with healthy controls (39,(68)(69)(70). IL6 is additionally associated with increased tumor size, tumor stage, metastases, and decreased survival (39).…”
Section: Inflammation and Vitamin D In Patients With Colorectal Cancermentioning
confidence: 99%
“…This association was highlighted by a study that measured the cytokine levels in the sera of CRC patients and identified a direct correlation between IL-6 expression levels and CRC progression (7). Furthermore, activation of the intracellular Janus kinase (JAK)/STAT3 signaling pathway by IL-6 results in the expression of various genes involved in cancer growth and development (8).…”
Section: Introductionmentioning
confidence: 98%
“…As shown in Fig 2.A, the relevance between high level of IL-17 + cells and histological grade (poor differentiation versus (vs.) well/moderate differentiation) was evaluated in 14 studies including head and neck cancers (HNC) (n = 2) [38,39], breast cancer (n = 1) [17], non-small-cell lung cancer (NSCLC) (n = 2) [40,41] and cancers of digestive system (n = 9) [16,20,28,[42][43][44][45][46][47], with 1645 patients. Results showed no statistical significance was found between high level of IL-17 + cells and histological grade (RR = 1.10, 95% CI [0.90, 1.34]).…”
Section: Il-17 + Cells and Histological Gradementioning
confidence: 99%
“…The association between high IL-17 + cells and lymph node metastasis was explored in 9 studies with 1074 patients [17,20,38,[42][43][44][45][46]48] (Fig 2.B). RR for the relevant 9 studies was 0.97 (95% CI [0.81, 1.15]), indicating the high IL-17 + cells within tumor tissues had no significant influence on lymph node status.…”
Section: Il-17 + Cells and Lymph Node Metastasismentioning
confidence: 99%
See 1 more Smart Citation